Safety and efficacy of the human neutrophil elastase inhibitor BAY 85-8501 for the treatment of non-cystic fibrosis bronchiectasis: A randomized controlled trial. (June 2019) - Watz, Henrik; Nagelschmitz, Johannes; Kirsten, Anne; Pedersen, Frauke; van der Mey, Dorina; Schwers, Stephan; Bandel, Tiemo-Joerg; Rabe, Klaus F.
Abstract: Background: There are only limited treatment options for patients with non-cystic fibrosis bronchiectasis (non-CF BE). Human neutrophil elastase (HNE) is a mediator of tissue destruction in non-CF BE. BAY 85-8501, a selective and reversible HNE inhibitor, could represent a new treatment option for this disease. Methods: This was a phase 2a, randomized, placebo-controlled, double-blind, parallel-group study. The primary objective was to assess the safety and tolerability of 1 mg BAY 85-8501 once daily (OD) for 28 days compared with placebo in patients with non-CF BE. Secondary objectives were to investigate the effects of 4 weeks of treatment with BAY 85-8501 on health-related quality of life, pulmonary function, and inflammatory and tissue damage biomarkers in sputum, blood and/or urine, and to evaluate the pharmacokinetics of BAY 85-8501. Results: Overall, 94 patients (mean age, 66 years; 53% male) were randomized (n = 47 per group), and 82 completed the study (BAY 85-8501, n = 37; placebo, n = 45). Treatment-emergent adverse events (TEAEs) occurred in 31 patients (66%) taking BAY 85-8501 and in 36 patients (77%) taking placebo, and were mostly mild or moderate. The serious TEAEs (BAY 85-8501, n = 3; placebo, n = 1) were not considered to be study-drug related. There were no changes in pulmonary function parameters from baseline to end of treatment, and health-related quality of life did not improve in any group. HNE activity in blood after zymosan challenge decreased significantly with BAY 85-8501 treatment (P = 0.0250 versus placebo). There were no significant differences in other biomarkers between treatment groups, with the exception of a small increase in interleukin-8 levels in sputum in the BAY 85-8501 group. Trough plasma concentrations of BAY 85-8501 plateaued after 2 weeks. Conclusions: 1 mg BAY 85-8501 OD had a favourable safety and tolerability profile when administered for 28 days to patients with non-CF BE. Further studies with a longer treatment duration are needed to evaluate the potential clinical efficacy in this study population.